First Report of Psoriatic-Like Dermatitis and Arthritis in a 4-Year-Old Female Spayed Pug Mix - Stephanie A. Regan; Rosanna Marsella; Ibrahim Ozmen (Case Reports in Veterinary Medicine)
Psoriasis manifests as chronic dermatitis and arthritis (PsA) in people. Psoriasis with concurrent PsA is characterized by erythematous, silvery, scaly plaques, especially on the extremities, and concurrent arthritis with enthesitis, tenosynovitis, and dactylitis. To date, no such disease has spontaneously occurred in domestic animals. This case report aims to describe the clinical, radiographic, and histologic appearance of a psoriasis-like dermatitis and psoriatic-like arthritis in a dog. A 4-year-old female spayed pug mix presented for the evaluation of chronic history of hyperkeratotic footpads and deforming arthritis. After ruling out other differential diagnoses and based on the similarity of clinical, radiographic, and histologic findings to human psoriasis and PsA, a tentative diagnosis of psoriasis-like disease was made. Treatment was begun to control pain (tramadol, gabapentin, and carprofen) and psoriatic dermatitis (clobetasol propionate 0.05%, calcipotriene 0.005%, and urea 40% ointment twice daily). Dramatic positive response to treatment was achieved confirming the tentative diagnosis. This case may provide preliminary evidence for the existence of a psoriasis-like condition in dogs and may elucidate treatment options in otherwise refractory cases of chronic dermatitis and polyarthropathy in dogs.